2003
DOI: 10.1128/iai.71.8.4516-4525.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Novel Factor Paa Involved in the Early Steps of the Adhesion Mechanism of Attaching and Effacing Escherichia coli

Abstract: Nonenterotoxigenic porcine Escherichia coli strains belonging to the serogroup O45 have been associated with postweaning diarrhea in swine and adhere to intestinal epithelial cells in a characteristic attaching and effacing (A/E) pattern. O45 porcine enteropathogenic E. coli (PEPEC) strain 86-1390 induces typical A/E lesions in a pig ileal explant model. Using TnphoA transposon insertion mutagenesis on strain 86-1390, we found a mutant that did not induce A/E lesions. The insertion was identified in a gene des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 55 publications
0
82
0
5
Order By: Relevance
“…Three of the genes (eae, paa and efa1tot) have been reported to be implicated in adhesion. [19][20][21] Due to gene clustering and correlations, the choice of single gene in a cluster to choose as a predictor is somewhat arbitrary. However, there are minor but significant differences in the contributions to sample and virulence classification.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the genes (eae, paa and efa1tot) have been reported to be implicated in adhesion. [19][20][21] Due to gene clustering and correlations, the choice of single gene in a cluster to choose as a predictor is somewhat arbitrary. However, there are minor but significant differences in the contributions to sample and virulence classification.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of e paa gene suggests its contribution to the early stages of PEPEC virulence (BATISSON et al, 2003) and its rPaa protein weights (PEREIRA et al, 2015b). In Paraná, 300 stool samples of 100 pigs from different farms were analyzed using PCR for the paa gene and its link to the enterotoxins Sta, Stb, and LT.…”
Section: Etiologymentioning
confidence: 99%
“…Recently, a study by Batisson et al [3] has identified and characterized a new factor involved in the adhesion mechanism of attaching and effacing in E. coli in swine. The gene was coined paa for porcine attaching and effacing-associated gene.…”
Section: East1 In Swinementioning
confidence: 99%